Effects of a minimal‐guided on‐line intervention for alcohol misuse in Estonia: a randomized controlled trial. (23rd July 2021) - Augsburger, Mareike; Kaal, Esta; Ülesoo, Triin; Wenger, Andreas; Blankers, Matthijs; Haug, Severin; Ebert, David D.; Riper, Heleen; Keough, Matthew; Noormets, Helen; Schaub, Michael P.; Kilp, Karin
Abstract: Background and Aims: Estonia has one of the highest alcohol‐attributable mortality rates within the European Union. The aim of this study was to estimate the efficacy of an on‐line self‐help intervention to reduce problem drinking at the population level. Design: On‐line open randomized controlled trial with an 8‐week intervention and an active control group (intervention n = 303, control n = 286). Assessments took place at baseline and at 6 months follow‐up. Setting: On‐ and offline channels were used for population‐based recruitment within a nation‐wide prevention campaign in Estonia. Participants: Inclusion criteria were age ≥ 18 years, heavy drinking [Alcohol Use Disorders Identification (AUDIT) test score ≥ 8], literacy in Estonian and at least weekly access to the internet; n = 589 participants were randomized (50% male, 1% other; mean age 37.86 years; 45% with higher level of education). Intervention and comparator: The intervention consisted of 10 modules based on principles of cognitive–behavioral therapy and motivational interviewing. The active control group received access to a website with a self‐test including personalized normative feedback and information for standard alcohol treatment. Measurements: The primary outcome was AUDIT scores at 6 months follow‐up adjusted for baseline scores. Findings: Intention‐to‐treat analyses were applied. Missing data were addressed by using baseline observation carried forward (BOCF) and multiple imputation by chained equations (MI); 175 completed follow‐up in the intervention group and 209 in the control group. AUDIT score at follow‐up was significantly smaller in the intervention [BOCF mean = 13.91, standard deviation (SD) = 7.61, MI mean = 11.03, SD = 6.55] than control group (BOCF mean = 15.30, SD = 7.31; MI mean = 14.30, SD = 7.21), with a group difference of −1.38 [95% confidence interval (CI) = –2.58, –0.18], P = 0.02 for BOCF and −3.26 (95% CI = –2.01, –4.51), P < 0.001 for MI. Conclusions: A randomized controlled trial has found that an on‐line self‐help intervention with minimal guidance was effective at reducing problem drinking in Estonia.